2018
DOI: 10.1186/s12966-018-0734-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term efficacy of a computer-tailored physical activity intervention for prostate and colorectal cancer patients and survivors: a randomized controlled trial

Abstract: BackgroundPhysical activity (PA) is beneficial in improving negative physical and psychological effects of cancer and cancer treatment, but adherence to PA guidelines is low. Computer-tailored PA interventions can reach large populations with little resources. They match with patients’ preference for home-based, unsupervised PA programs and are thus promising for the growing population of cancer survivors. The current study assessed the efficacy of a computer-tailored PA intervention in (four subgroups of) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
243
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(249 citation statements)
references
References 89 publications
2
243
1
3
Order By: Relevance
“…The trials were published between 2005–2018. Trials were undertaken in the USA (Bantum et al, ; Owen et al, ; Smith et al, ; Somers et al, ; Syrjala et al, ), Netherlands (Admiraal et al, ; van der Berg et al, ; Boele et al, ; Golsteijn et al, ; Willems et al, ), UK (Foster et al, ), Canada (Vallerand et al, ), China (Zhang et al, ; Zhu et al, ), and South Korea (Lee et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The trials were published between 2005–2018. Trials were undertaken in the USA (Bantum et al, ; Owen et al, ; Smith et al, ; Somers et al, ; Syrjala et al, ), Netherlands (Admiraal et al, ; van der Berg et al, ; Boele et al, ; Golsteijn et al, ; Willems et al, ), UK (Foster et al, ), Canada (Vallerand et al, ), China (Zhang et al, ; Zhu et al, ), and South Korea (Lee et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Participants in four trials were patients with any cancer (Foster et al, ; Bantum et al, ; Somers et al, ; Willems et al, ). The other eleven trials focused on specific cancers: breast cancer (Admiraal et al, ; van den Berg et al, ; Lee et al, ; Owen et al, ; Smith et al, ; Zhu et al, ), glioma (Boele et al, ), haematological cancer (Syrjala et al, ; Vallerand et al, ), rectal cancer (Zhang et al, ), and both colorectal cancer and prostate cancer (Golsteijn et al, ). Nine trials reported participants who completed primary treatment (Admiraal et al, ; van der Berg et al, ; Foster et al, ; Lee et al, ; Bantum et al, ; Somers et al, ; Syrjala et al, ; Willems et al, ; Zhang et al, ); the time since treatment completion was 4 weeks to 18 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations